Home Teachers in the Lublin Province from 1832 to 1864: An Attempt to Describe Their Characteristics - Monika Hajkowska (Studia Paedagogica Ignatiana, 2017)
The aim of this article is to present the issue of teachers and home teachers in the Lublin Province from 1832 to 1864. The subject of the study is a group of people undertaking home-based teaching in private homes. The aim of this study has been to characterize this occupational group, including its number, age, gender, nationality. In addition, an analysis of the school authorities’ regulations concerning its control, examinations and certificates of the employment and the occupational status was made. The authorities of the Kingdom of Poland took steps to control this professional group from 1833 onwards. With the introduction of the Highest-Approved Act for the private research institutes, the governesses and home teachers in the Kingdom of Poland in 1841, this control became more intense. Pursuant to the provisions of the Act, the headmasters of secondary schools were obliged to submit annual reports to the Curator of the Warsaw Educational District about those undertaking the profession of a home teacher. In practice, significant problems were encountered in their preparation. The home teachers did not report to the school authorities about taking up private home duties for fear of coming under greater control and being fined. Many of them did not possess the required certificates, authorizations or permissions. The regulation concerning the obligation to provide the competent school authorities with information about any change of workplace, to submit a statement from home in which they performed their duties and certificates of competency was not respected. Teachers were not the only ones who did not adopt the school authorities’ recommendations. The calls for people hiring home teachers to report it were not always effective.